(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
The report presents some experimental studies carried out by sawing of logs with narrow band saw blades in winter conditions. The experiments were carried out in manufacturing con-ditions in February. For the purpose a horizontal band saw "Wirex CZ-1/ZM" was used. Operating conditions were established and the quality of sawn lumber from semi frozen logs of Douglas fir (Pseudotsuga menziesii (Mirb.) Franco) was tested. The quality preparation of the band saw blade with the used horizontal band saw provides good parameters of the sawn lumber: surface roughness R̅m = 190 μm; variation in the accuracy of the size and shape of 1.5 mm and 1.8 mm at a feed speed of U = 11.5 m.min-1.